Significant enhancement in thermoelectric performance of Mg3Sb2 from bulk to two-dimensional mono layer. (August 2019) - Huang, Shan; Wang, Ziyu; Xiong, Rui; Yu, Hongyu; Shi, Jing
Abstract: Thermoelectric materials can effectively convert waste heat into electrical energy and receive more and more attention. Zintl phase Mg3 Sb2 is a typical layered thermoelectric material and the anisotropy in crystalline structure induces strong anisotropy in its thermoelectric properties. As a result, polycrystalline Mg3 Sb2 usually can not achieve the maximum thermoelectric performance. Our research proves that the dimensionality reduction in material structure can not only avoid certain crystalline direction's poor thermoelectric properties but also effectively reduce the lattice thermal conductivity. Within the framework of the density functional theory, the thermoelectric performance of two-dimensional Mg3 Sb2 mono layer is accurately investigated. The ZT value of the Mg3 Sb2 nano-thin film can reach 2.5 at 900 K, which is larger than that of the bulk. The theoretical results indicate that the process of nano-engineered structure can significantly enhance the energy conversion efficiency of thermoelectrics. Graphical abstract: Image 1 Highlights: For the first time, the structure of nano-thin Mg3 Sb2 mono layer has been established. The thermoelectric properties of Mg3 Sb2 bulk and mono layer have been calculated systematically and accurately. The figure of merit ( ZT ) of nano-thin Mg3 Sb2 mono layer exceeds 2.0 at high temperature region. Provide evidences for enhancing thermoelectric conversion efficiency by nano-engineered structural technology.